Development and application of a borehole stress meter in rocks surrounding the roadway, based on optical-fiber sensing technology - Xie, Xiaoping; Fang, Xinqiu; Liu, Hongyang; Xing, Xiaopeng; Liang, Minfu; Wu, Gang; Chen, Ningning (Frontiers in Earth Science, 2023)
Stress in rock masses is an important parameter in the design and construction of underground engineering, such as the design and maintenance of mine roadways and the design of mining working faces. It is also a fundamental force causing the deformation and failure of geotechnical engineering excavation. At present, the abutment-pressure monitoring technology of the surrounding rocks of the coal mine roadway in China is not intelligent and systematic and lacks some high-precision sensing instruments and multi-functional monitoring systems. The mechanical model of the rocks surrounding the borehole was constructed by theoretical analysis of problems in the stress monitoring technology for underground rock masses in coal mines. Additionally, the interaction between the surrounding rocks and the borehole stress meter was analyzed. The borehole stress meters for tubular-structure fiber Bragg grating (TS-FBG) and cystic-structure fiber Bragg grating (CS-FBG) were designed by combining the sensing principle and sensing characteristics of fiber Bragg grating, and the performance of the two kinds of fiber Bragg grating borehole stress meters was compared by laboratory test. The track roadway of the 14,301 tested working faces in the Shaqu Coal Mine was taken as an example, and the stress of the rocks surrounding the 14,301-track roadway was monitored in real time by CS-FBG borehole stress meter during the mining of the working face. The following conclusions are drawn from the field application. The rig-site utilization results revealed obvious stress growth and stress peak zones in the mining-stress change curves of each measuring point on the two sides of the 14,301-track roadway in the process of mining the tested working face. Additionally, there were four stages: rapid rise, uniform growth, rapid rise to the peak, and rapid decline. Maximum stress monitored by the second station was 18.5 MPa, and the influence range of stress was over 140 m. Maximum stress monitored by the first measuring station was 19 MPa, the influence range of stress was about 80 m, and the peak stress position was about 20 m in front of the coal wall. Rig-site utilization proved the design of the CS-FBG borehole stress meter to be reasonable. Performance was stable and reliable, and the successful operation of field monitoring achieved the expected effect.